A framework for cancer health economics research. Issue 7 (25th November 2020) - Halpern, Michael T.; Shih, Ya‐Chen Tina; Yabroff, K. Robin; Ekwueme, Donatus U.; Bradley, Cathy J.; Davidoff, Amy J.; Sabik, Lindsay M.; Lipscomb, Joseph
Abstract : Lay Summary: Cancer has substantial economic impacts for patients, their families and/or caregivers, employers, and the health care system. However, there is only limited understanding of how economic issues can affect access to cancer care services and the receipt of high‐quality cancer care. Health economics research in cancer is particularly timely due to the large and increasing number of patients with cancer and cancer survivors, but there are many factors that may create barriers to performing cancer health economics research. This commentary has identified important topics and questions in cancer health economics research and will assist in the development of this critical field. Abstract : Although economic constructs influence the delivery of cancer‐related services, and cancer and its treatment have substantial economic consequences, to the authors' knowledge there is only limited understanding of how economic considerations affect health care delivery, health equity, quality of cancer care, and other cancer outcomes. This commentary presents a framework to help identify important topics and research questions in cancer health economics research and to assist in the development of this critical field.